Aljamu’u dan Al-Tarjih Dalam kedudukan Hadits Ibadah Perspektif Sedekap, Qunut Muslim Maluku Utara - Hamzah Umasugi, S.Pd.I,.M.Pd.I (Sekolah Tinggi Agama Islam Babussalam Sula, 2023)
Islam is the religion of Rahmatan Lil Alameen! In religious practice, Muslim communities always refer to multiple sources of law as rules that are actually enforced by divine beings. The Quran and As-Sunnah are the solid and complete basic foundations of religion. This is reflected in the meaning of the hadiths which are the second source of law from the Quran, with disputes over the interpretation of the hadiths often leading to different viewpoints between Ikhtilaf groups. The various ideas that emerged with the fanaticism of the schools of thought regarding the implementation of prayer in the sense of Sedekaap and Qunet spread to the polarization of life, including politics, social and culture, where interpretations emerged. Lessons on the concepts of fiqh. To look at the conflicting religious hadith controversies in North Maluku, the author uses a phenomenological approach to explore the factual forms of sedakaf and qunat practices as seen from contemporary political, social, cultural and even fiqh studies. Key words: Hadith Ibadah, Sedekaaf, Qunut